â€œI am Going Homeâ€: How Kenyan Migrantsâ€™ Intentions to Return Home Affect their Transnational Engagements - Jane Njeri Mwangi; Alex Boakye Asiedu (African Human Mobility Review, 2021)
The aim of this study is to examine how Kenyan migrants’ intentions to return home influence their participation in transnational activities like sending remittances, investments and return visits. In this study, our focus is on Kenyans living in the UK, USA, Canada and Ghana. A concurrent mixed method approach was used in data collection and analysis. This included a web survey of 212 respondents, 21 in-depth interviews and 5 focus group discussions. Most (89%) of the respondents intended to return to Kenya before retirement but difficulty in finding well-paying employment, insecurity, corruption, citizenship issues and reintegration uncertainties were seen as obstacles to return. Incentives for return included a better economic and political environment, improved security, good governance, employment and investment opportunities. Overall, the study revealed that migrants’ intentions to return home had an influence on their participation in remittance transfers, investments and return visits. Cross tabulations, odd ratios and chi square logistic regression analyses showed that intentions to return had an influence on migrants’ investments in entrepreneurial ventures and financial instruments, as well as the frequency of return visits to Kenya.